2015
DOI: 10.4103/0970-4388.155136
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint ankylosis in child: A case report

Abstract: The treatment of TMJ ankylosis poses a significant challenge because of technical difficulties and a high incidence of recurrence. Its treatment includes the orthodontist, oral and maxillofacial surgeon, pediatric dentist, and psychologist and physical therapist as part of the healthcare team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
1
1
Order By: Relevance
“…The patients in the study dominantly presented with micrognathic deformities which coincide with de Castro e Silva et al results, conversely it is in contrast with Liaqat et al results in which the patient presented with retrognathia and Rahul Hegde et al findings in which the patient presented with both micrognathia and retrognathia [17][18][19].…”
Section: Treatment Number Percentagecontrasting
confidence: 55%
“…The patients in the study dominantly presented with micrognathic deformities which coincide with de Castro e Silva et al results, conversely it is in contrast with Liaqat et al results in which the patient presented with retrognathia and Rahul Hegde et al findings in which the patient presented with both micrognathia and retrognathia [17][18][19].…”
Section: Treatment Number Percentagecontrasting
confidence: 55%
“…Similarly, Hegde et al . 7 reported history of trauma as a cause of ankylosis in a 12-year-old patient, and Gupta et al 8 also found trauma as the most common cause of ankylosis in 90% of surveyed children. In the present case Interpositional arthroplasty was done under G.A with postoperative physiotherapy to prevent reankylosis, which was consistent with a similar study done by Hegde et al 7 and Goel et al 9…”
Section: Discussionmentioning
confidence: 98%
“…Temporomandibular joint ankylosis, which refers to immobility secondary to ankylotic fusion of the mandible to the cranial base or zygoma, is a disabling condition itself [Lima et al, 2011;Hegde et al, 2015]. If associated with CFZS, temporomandibular joint ankylosis worses hypotonia and facial palsy in limiting the mouth opening.…”
Section: Discussionmentioning
confidence: 99%